UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN MATEMATIKA KELAS 1 SDN SILIH ASUH 2 - Rizka Karima Meilin, Rima Hildayanti, Risna Septiana; Eline Rozaliya Winarto, Ika Muslika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest and learning outcomes of first grade students of SDN Silih Asuh 2 in Mathematics, especially in the material on measuring length using non-standard units. Students are less active in learning, do not understand the concept of length, and have difficulty in measuring and comparing the length of objects. The purpose of this study is to improve students' interest and learning outcomes through the application of the Problem Based Learning (PBL) learning model. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages, namely planning, implementing actions, observation, and reflection. The subjects of the study were 20 first grade students of SDN Silih Asuh 2. Data collection techniques used include observation, documentation, and learning outcome tests. The results of the study indicate that the application of the Problem Based Learning model can improve students' interest and learning outcomes. In the pre-cycle stage, only 7 students (35%) achieved scores above the Minimum Completion Criteria (KKM). After the implementation of the PBL model, the number of students who completed the program increased to 13 students (65%) in cycle I, and reached 18 students (90%) in cycle II. In addition, students became more active, enthusiastic, and involved in the learning process. Thus, it can be concluded that the Problem Based Learning